Hypertension-Mediated Organ Damage in Relation to Severity of Chronic Low Back Pain in Hypertensive Patients - Maciej Skrzypek; Rafał Kolec; Michał Słaboszewski; Katarzyna Góra; Agnieszka Olszanecka; Piotr Wróbel; Katarzyna Stolarz-Skrzypek; Marek W. Rajzer (Journal of Cardiovascular Development and Disease)
Introduction: Chronic pain triggers a stress response, which results in increased blood pressure (BP). We investigated whether chronic low back pain (cLBP) in hypertensive patients is associated with an increased risk of hypertension-related organ damage. Methods: We studied 85 consecutive hypertensive patients with a median age of 62 years (55–67), who suffered from cLBP, the severity of which was evaluated according to the Oswestry Disability Index (ODI). Patients underwent transthoracic echocardiography, arterial ultrasonography and vascular tonometry. We assessed carotid artery atherosclerotic plaques, along with carotid-femoral pulse wave velocity (cf-PWV) and left ventricular mass index (LVMI). Results: An equal to or higher than median (16 points) ODI score in 48 subjects (56.5%) was associated with the presence of carotid artery plaques (p = 0.014). In multivariate analysis, after adjusting for covariates, the presence of carotid artery plaques remained independently associated with an ODI score equal to or higher than the median (OR, 3.71; 95% CI, 1.04–13.25; p = 0.044). None of the other analyzed parameters of hypertension-related organ damage demonstrated a significant relationship with the ODI score. Conclusions: We observed that more severe cLBP is associated with a higher prevalence of carotid artery atherosclerotic plaques among hypertensive patients.